PENGARUH UTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Rosita, Maizah; Gantino, Rilla (Program Studi Akuntansi FPEB UPI, 2017)
The purpose of this research is to determine the effect of The Debt (Long Term Liabilities to Total Assets and Liabilities Total Assets) to the return on assets, return on equity and earning per share. The research used secondary data from annual financial report of Food Beverage Company from 2011-2015 listed on BEI, used purposive sampling method and used multiple regression analysis. Based on the test result of simultan or test F The Long Term Liabilities to Total Assets and Short Term Liabilities is significant to the Return On Assets, Return On Equity and Earning per share. Result of partial test or T Test, Long Term Liabilities to Total Assets is not significant on Return On assets, Short Term Liabilities to Total Assets is significant on Return on Assets. Long Term Liabilities to Total Assets is not significant to Return On Equity, Short Term Liabilities to Total Assets significant to Return On Equity, Long Term Liabilities to Total Assets in not significant to Earning per share, and Short Term Liabilities to Total assets is significant to Earning per share.